2021
DOI: 10.1186/s12960-021-00682-0
|View full text |Cite
|
Sign up to set email alerts
|

Practices and resilience of dieticians during the COVID-19 pandemic: a national survey in the United Arab Emirates

Abstract: Background The COVID-19 pandemic impacted the practices and resilience of most healthcare workers, including dieticians. In addition to offering critical care to COVID-19 patients, dieticians play a major role in preventing and managing conditions known to affect COVID-19, such as obesity and metabolic disorders. The objective of this study was to examine the conditions and changes in the work environment as well as resilience and its correlates among dieticians during the COVID-19 pandemic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…In addition, COVID-19-associated discrimination was positively correlated with turnover intention, as it contributed to aggravating factors, such as poor mental health and burnout [ 44 ]. On the other hand, resilience within HCWs was found to be negatively correlated with turnover intention [ 27 29 , 52 ], with two studies concluding that it acted as a protective mechanism against factors that contributed to turnover intention [ 43 , 44 ]. Professional commitment and job satisfaction were other psychological factors that were associated with reduced turnover intention within nurses and physicians, respectively [ 26 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, COVID-19-associated discrimination was positively correlated with turnover intention, as it contributed to aggravating factors, such as poor mental health and burnout [ 44 ]. On the other hand, resilience within HCWs was found to be negatively correlated with turnover intention [ 27 29 , 52 ], with two studies concluding that it acted as a protective mechanism against factors that contributed to turnover intention [ 43 , 44 ]. Professional commitment and job satisfaction were other psychological factors that were associated with reduced turnover intention within nurses and physicians, respectively [ 26 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have identified barriers to nutrition care practice and reported on changes in the work environment as well as resilience levels of dietitians during the COVID-19 pandemic. However, research evaluating the impact of the pandemic on the personal health of dietitians is lacking [16,17]. This present study seeks to represent RDNs in emerging research and uncover new information on the influence of stress and life disruption on these professionals' weight, health habits, psychological factors, and professional practices, and on whether professional training as an RDN can be perceived as a protective factor in maintaining healthy habits.…”
Section: Introductionmentioning
confidence: 99%
“…Dietitians, who serve as the foundation of any healthcare facility, have made significant contributions to the COVID-19 pandemic response [9]. Dietitians are specialists in determining the patient's dietary needs while considering the patient's age, gender, and any other underlying medical issues that may exist [10]. Nutrition is critical in assisting COVID-19 patients in fighting the infection and rapid recovery in the in-patient and out-patient settings [11].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, dietitians have shouldered additional responsibilities that are deemed outside of their typical responsibilities, such as screening for COVID-19, and starting new duties in the Intensive Care Unit (ICU) [14]. According to a recent study [10], 40% of dieticians left their jobs due to the COVID-19 pandemic. Others claimed that trying to maintain a work-life balance while working in such a pandemic was the toughest for them [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation